ROJA HAMA-HAMA? TINJAUAN LINGUISTIK TRADISI TENUN ENDE DAN PALU'E (Roja Hama-hama? A Linguistic Review of The Ende and Palu'e Weaving Traditions) - Danerek, Stefan (Jurnal Lingko : Jurnal Kebahasaan dan Kesastraan, 2021)
The study of loom technology and textile design structure can reveal connections between weaving traditions similarly to how comparative linguistics reveal connections between linguistic groups, due to the inherent conservatism of weaving. This paper compares the weaving traditions of the Ende and the Palu’e, who are linked in oral traditions, primarily by comparing weaving related terminology against the dictionary, and examines if Palu’e weaving have branched away from Ende weaving. The archaic style of Palu’e weaving may have a source in older forms of Flores design structures that became surpassed by developments, such as patola designs among the Ende. But the comparison of the weaving lexicons show a lower convergence than language generally and does not support a Palu’e weaving origin from the Ende, neither do the designs and basic techniques. The links between the Ende and the Palu’e are more on the proto-level; language group, culture, weaving tools. Studi tentang teknologi alat tenun dan struktur desain tekstil dapat mengungkapkan hubungan antara tradisi menenun serupa linguistik komparatif mengungkapkan hubungan antara kelompok linguistik, karena konservatisme inheren tradisi tenun. Artikel ini membandingkan tradisi tenun Ende dan Palu'e, dua kelompok yang terkait dalam tradisi lisan, terutama dengan membandingkan terminologi tenun dengan kamus, dan menguji apakah tenun Palu’e pernah bercabang dari tenun Ende. Gaya kuno tenun Palu’e mungkin memiliki sumber dalam bentuk struktur desain Flores zaman dahulu yang dilampaui perkembangan seperti desain patola di tradisi Ende. Tetapi perbandingan leksikon tenun menunjukkan konvergensi yang lebih rendah daripada bahasa pada umumnya dan tidak mendukung bahwa tenun Palu’e pernah bercabang dari tenun Ende, begitu pula desain dan teknik dasarnya. Hubungan antara Ende dan Palu lebih pada tingkat proto; kelompok bahasa, budaya, alat tenun.